2009
DOI: 10.2319/021308-87.1
|View full text |Cite
|
Sign up to set email alerts
|

Increased Occurrence of Dental Anomalies Associated with Second-Premolar Agenesis

Abstract: Objective: To evaluate the prevalence of dental anomalies in patients with agenesis of second premolars and compare the findings with the prevalence of these anomalies in the general population. Materials and Methods: A Brazilian sample of 203 patients aged 8 to 22 years was selected. All patients presented agenesis of at least one second premolar. Panoramic and periapical radiographs and dental casts were used to analyze the presence of other associated dental anomalies, including agenesis of other permanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
1
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 18 publications
6
67
1
10
Order By: Relevance
“…These results support those of several researchers who have demonstrated close associations between M3 agenesis and asymmetrical or symmetrical agenesis of maxillary and mandibular Is and P2s (4,6,9,10,14,16). Our results suggest that the phenotype represented by symmetrical agenesis of mandibular M3s is concurrent with high prevalence rates of agenesis of maxillary I2s and maxillary and mandibular P2s in the same subjects.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results support those of several researchers who have demonstrated close associations between M3 agenesis and asymmetrical or symmetrical agenesis of maxillary and mandibular Is and P2s (4,6,9,10,14,16). Our results suggest that the phenotype represented by symmetrical agenesis of mandibular M3s is concurrent with high prevalence rates of agenesis of maxillary I2s and maxillary and mandibular P2s in the same subjects.…”
Section: Discussionsupporting
confidence: 81%
“…There is enough evidence to indicate that agenesis of the maxillary and mandibular second premolars (P2s) and lateral incisors (I2s) is frequently associated with M3 agenesis (9)(10)(11)(12). Some investigators have demonstrated associations among symmetrical agenesis of the maxillary first molars (M1s) with P2 agenesis, symmetrical agenesis of M3s, and advanced tooth agenesis (13).…”
Section: Introductionmentioning
confidence: 99%
“…In selecting discrete anomalies for study, we included four categories that previously have been shown to be directly associated with infraocclusion to test whether our infraocclusion sample indeed manifested the same previously noted associations: any tooth agenesis (except M3) and the premolar agenesis subgroup, [15][16][17][18][19][20][21] PDC, 18 and microdontia of maxillary lateral incisors. 18 More significantly, two dental anoma- The results showed a clear and statistically significant increase in prevalence of the four previously reported and the two newly added anomaly categories among subjects with infraocclusion, compared with their reported prevalence in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Further corroboration of genetic etiologic factors comes from studies showing that infraocclusion is an abnormality frequently observed accompanying the presence of other dental anomalies. [13][14][15][16][17][18][19][20][21] Abnormal conditions such as tooth agenesis, microform teeth, delayed tooth development, palatally displaced canines (PDC), and mandibular second premolar distal angulation (MnP2-DA) have been found to occur together much more frequently than would be expected by chance. Combinations of these occurrences have been named dental anomaly patterns (abbreviated as DAP) by Peck 22 and form an important part of the problem list for 10% to 20% of orthodontic patients diagnosed with malocclusion.…”
Section: Introductionmentioning
confidence: 99%
“…In case of agenesis of at least 1 premolar, deciduous molar infra-occlusion is more frequent, at 24.6% 8 . It results from arrested deciduous eruption without physical obstacle after emergence 2 : the infra-positioned tooth remains stationary while surrounding growth continues (Fig.…”
Section: Introductionmentioning
confidence: 99%